The Effect of Functional Analysis Technique in Reducing Costs under the Strategic Approach to Cost Management - Nashid, Qasim Habeeb; Ali, Ahmed Maher Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
Strong competition between economic units is the most noticeable thing about the business world today. Because of this competition, traditional cost management systems can’t provide information that helps economic units in general and Iraq in particular meet the new requirements that focus on customer satisfaction. This led to the creation of There was a need for a strategic technique that helps break down a product into its features and functions in a way that allows the economic unit to cut costs without having to change the quality the customer wants. There was also a need for information with a strategic dimension that would help the economic unit make decisions in a unique way. Adopting one strategy without another is hard. The current research aims to show the impact of adopting the technique of functional analysis and strategic cost management to reduce product costs to achieve customer satisfaction with product functions and quality. The research method was based on the use of the (SPSS) program with a reliability and stability coefficient of (91%).Where the results of the statistical analysis indicated the highest mean (4.2) and the coefficient of variation of (20.66) within the percentage weight of (77.14) indicating that the compatibility of functional analysis and the strategic approach to cost management works to eliminate and enhance the value At the lowest total cost by providing the level of performance that the customer expects from the sample size of (35) workers in the Kufa Cement Factory.As for the most important recommendations, it was suggested that the economic unit should achieve a balance between the values from the customer’s point of view and the values from the economic unit’s point of view by providing products with high quality functional benefits and low cost so that they can meet the customer’s needs as well as the goal sought by the management of the economic unit of adding value and making profits.